2022
DOI: 10.5296/jei.v8i2.20418
|View full text |Cite
|
Sign up to set email alerts
|

Development of Problem-Solving Abilities in Science by Inquiry-Based Learning With Cooperative Learning for Grade 4 Students

Abstract: Considering problem-solving ability as an important qualification in the 21st century that could be developed by instructional methods that allow learners to construct their knowledge via questioning through cooperative learning activities, we conducted action research with the purpose of investigating the effectiveness of inquiry-based and cooperative learning on grade 10 students’ problem-solving ability and studying students’ satisfaction with inquiry-based and cooperative learning in developing their probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The students sought knowledge by themselves with an average score was 4.77, and the students were happy in their studies with an average score of 4.77 and found that students were least satisfied with the content in the lesson is a sequence of steps and easy-to-understand with an average score of 4.15. This is a result of the researcher having organized activities that allow students to study, research, and exchange ideas, as well as encouraging students to learn from real problem situations, which satisfied the students at the level of agreement [41], [42].…”
Section: Resultsmentioning
confidence: 99%
“…The students sought knowledge by themselves with an average score was 4.77, and the students were happy in their studies with an average score of 4.77 and found that students were least satisfied with the content in the lesson is a sequence of steps and easy-to-understand with an average score of 4.15. This is a result of the researcher having organized activities that allow students to study, research, and exchange ideas, as well as encouraging students to learn from real problem situations, which satisfied the students at the level of agreement [41], [42].…”
Section: Resultsmentioning
confidence: 99%
“…A solution with a dissociation percentage of 100%, pH = 11.25, volume 45 cm 3 of metal with atomic number 55 as element, was titrated with the HF solution with a dissociation constant of 6.6 × 10 -4 and pH = 5.87, volume 55 cm 3 2. Two researchers evaluate the phase of implementing the specified approach Application strategy f % The correct approach, the right answer 56 63 The correct approach, the wrong answer 33 37 The erroneous approach, the right answer 0 0 The erroneous approach, the wrong answer 0 0…”
Section: Discussionmentioning
confidence: 99%
“…Finding a workable solution or a way to the desired outcome involves systematic observation and critical analysis as part of the problem-solving process. Problem-solving is the process of learning information and the ability to assist the country's government by interfering with a set of procedures and objectives when the answer is unknown, unfamiliar, or reaches a new state of aim [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Konsep utama pembelajaran kooperatif adalah kerjasama yang ketika individu bekerja sama dalam kelompok untuk mempromosikan baik hasil belajar individu maupun kelompok (Odehova et al, 2022). Siswa memiliki kemampuan untuk berinteraksi dengan teman sekelas, menyampaikan dan mempertahankan gagasan, berbagi perspektif yang berbeda, dan mempertanyakan kerangka kerja konseptual di kelas (Sukontawaree et al, 2022).…”
Section: Pendahuluanunclassified